2017
DOI: 10.1097/iae.0000000000001206
|View full text |Cite
|
Sign up to set email alerts
|

Closing Macular Holes With “Macular Plug” Without Gas Tamponade and Postoperative Posturing

Abstract: Twenty-three-gauge pars plana vitrectomy combined with broad ILM peeling, use of ILMR and autologous gluconated blood clumps as a macular plug is effective in achieving satisfactory hole closure with statically significant functional improvement for large Stage 3 and Stage 4 macular holes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 29 publications
0
33
1
4
Order By: Relevance
“…Although we could not obtain data of the duration of MHs, the results may be because important components of the retina probably had degenerated during the period of the MH. Chakrabarti et al (2017) treated MHs by gluconated blood clumps without gas tamponade or postoperative posturing, and they reported that the visual recovery was good after surgery even for large MHs which is not consistent with our results. However, the basal diameter of MH in their study was 892.8 lm, while it was 1036 lm in our study (Table 1).…”
Section: Discussioncontrasting
confidence: 88%
“…Although we could not obtain data of the duration of MHs, the results may be because important components of the retina probably had degenerated during the period of the MH. Chakrabarti et al (2017) treated MHs by gluconated blood clumps without gas tamponade or postoperative posturing, and they reported that the visual recovery was good after surgery even for large MHs which is not consistent with our results. However, the basal diameter of MH in their study was 892.8 lm, while it was 1036 lm in our study (Table 1).…”
Section: Discussioncontrasting
confidence: 88%
“…41 Similarly, autologous whole blood, serum and platelet concentrates, thrombin, and gluconated blood clumps have been used in various studies with variable outcomes. [42][43][44][45][46][47][48] These adjuvant agents circumvent the use of ILM peeling, thus minimizing the retinal trauma and obviate the need for any tamponade agents or postoperative positioning. However, the benefit of these adjuvants has not been proven in large studies.…”
Section: Adjuvant Agentsmentioning
confidence: 99%
“…The fresh blood soon became a clot on the surface of the ILM within 1-2 min and followed by intravitreous injection of C3F8. Autologous blood clot has also been reported to assist the inverted ILM technique [6] and the treatment of MH retinal detachment [19]. Our findings indicated that silicon oil could be replaced by autologous blood clot to avoid the displacement of the transposition ILM after surgery.…”
Section: Discussionmentioning
confidence: 62%
“…The inverted ILM flap technique, first reported by Michalewska et al [4], has shown improved functional and anatomical outcomes for those cases. This technique was then modified by injecting viscoelastic into the MH as a "viscoelastic cap" or employing autologous gluconated blood clumps as a "macular plug" to facilitate the closure of MH [5,6]. For the recurrent MH, Park et al [7] used a free ILM flap, which was collected from the residual ILM, to cover the MH with the assistance of perfluoro-n-octane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation